Intercultural Interpretation of the “Good Shepherd” within the Indonesian Context - Roberthus Kalis Jati Irawan; Frederick Ray Popo; Andreas Agung Nugroho; Barry Ekaputra; Nikolas Kristiyanto (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Inculturation permeates the life of the Catholic Church since its conception, making it stay relevant and creative with its evangelising mission amidst a multicultural world. This paper is a study of inculturation within the discipline of biblical exegesis. After a brief explanation about the essence of inculturation, it explores some forms of popular intercultural exegesis or contextual hermeneutics which was developed in Africa. One of them is the “four-legged stool” method designed by Elizabeth Mburu. We applied Mburu’s method to interpret the image of the “good shepherd” which was used by Jesus in John’s Gospel narrative (Jn. 10:1-12), a familiar passage to most Indonesian Catholics. Mburu’s method puts the metaphor align with the theological, literary, and historical context of the local reader. In this case, the research considers the meaning of “a good shepherd” understood through the Indonesian mindset. As a result, the biblical metaphor gained extra meaning from native roots.